Effect of yellow capsicum extract on the lipid metabolism in mice - CUI Xiaoman; YU Haining; XU Jielan; CHEN Zhongting; SHEN Shengrong (浙江大学学报. 农业与生命科学版)
Presently, obesity is not only becoming a critical medical problem worldwide but also will cause lots of obesity-related chronic diseases as well, like hypertension, cardiovascular diseases, diabetes and so on. It becomes more and more important for current scientists to explore the effective pathway to solve the puzzle. Many researchers from different countries put much more emphasis on the anti-obesity effect of natural products. There are many studies showing that the extracts of certain parts of varied kinds of natural plants are able to inhibit the obesity through the influences on lipids metabolism, adipocytes secretion and show prevention effects on obesity through animal tests. Yellow capsicum includes functional component capsaicin which has multifunctional pharmaceutical effects. In the present study, the anti-obesity action of yellow capsicum extract (YCE) was investigated through their intervention effect on lipids metabolism in C57BL/6J mice.The total thirty-two mice were divided into four groups, including control group, obesity model group and YCE treatment groups at doses of 100 and 25 mg/kg body mass. The mice in control group were fed with normal diet and those in other groups were fed with hyperlipidic diet and YCE at different doses once a day for 40 consecutive days. All mice were weighed every five days and their body mass were recorded. In the end, the mice were killed and dissected, body fat percentage, contents of total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL) and leptin in serum, expression levels of TC, TG, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in the liver, were all detected and analyzed. Besides, the pancrelipase (PL) level of pancreatic tissue was also detected through ELISA method, as it is an important lipase in lipids metabolism.The results showed that, after 40 days' treatment through hyperlipidic diet, the obesity model group was successfully built up, as they were overweighed (P<0.01) and showed a higher mass of adipose tissue (P<0.05), TC (P<0.05), TG (P<0.01) contents than the normal diet control group. Compared with obesity model group, YCE exhibited an inhibitory effect on body mass to some extent (P < 0.01), fat tissues, body fat percentage (P<0.01) and Lee's index declined (P<0.05). The contents of TC, TG and LDL of the serum in YCE treatment groups were declined (P<0.01), while there was no difference in HDL level. The liver mass (P<0.01) and its TG contents (P<0.05) in YCE treatment groups were lower than that of obesity model group. Meanwhile, TC content exhibited no significant change, on the other hand, the AST and ALT levels in the liver were normal, it showed that the YCE treatment had no side-effect on liver tissues. The PL level in YCE treatment groups was decreased (P<0.05) and it indicated that YCE might act on PL to affect lipidolysis.From the above tests we can conclude that YCE has a significant anti-obesity effect. The changes in blood and liver indices, like TC, TG and so on, reflects its intervention on lipids metabolism. Moreover, YCE has no side-effect on liver tissues. Also YCE has a potential inhibitory effect on Pancrelipase (PL), which can be a potential target for anti-obesity therapy. Our results provide a further research evidence and basis for YCE's deep exploration and development.